2014
DOI: 10.1007/s00779-014-0829-5
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phones as medical devices in mental disorder treatment: an overview

Abstract: Mental disorders can have a significant, negative impact on sufferers' lives, as well as on their friends and family, healthcare systems and other parts of society. Approximately 25 % of all people in Europe and the USA experience a mental disorder at least once in their lifetime. Currently, monitoring mental disorders relies on subjective clinical self-reporting rating scales, which were developed more than 50 years ago. In this paper, we discuss how mobile phones can support the treatment of mental disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
125
0
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(136 citation statements)
references
References 76 publications
0
125
0
11
Order By: Relevance
“…This makes mobile phones a viable platform for mental illnesses diagnosis and management [7,18]. Among the pioneer projects, the MONARCA project used a variety of phone sensors such as GPS and accelerometer to detect the mental states as well as changes in mental states of bipolar patients [9]. In their study that involved 12 patients over a period of 12 weeks, they have shown that mobile behavioral sensing system could identify both depression and mania states with an accuracy of more than 70% and detect state-change with very high precision and recall [10] .…”
Section: Related Workmentioning
confidence: 99%
“…This makes mobile phones a viable platform for mental illnesses diagnosis and management [7,18]. Among the pioneer projects, the MONARCA project used a variety of phone sensors such as GPS and accelerometer to detect the mental states as well as changes in mental states of bipolar patients [9]. In their study that involved 12 patients over a period of 12 weeks, they have shown that mobile behavioral sensing system could identify both depression and mania states with an accuracy of more than 70% and detect state-change with very high precision and recall [10] .…”
Section: Related Workmentioning
confidence: 99%
“…Smart medical industries emphasize users' intelligence and experiences, an efficient treatment plan evaluation is facilitating these industries sharply [10,11]. During the evaluation of a treatment plan, users usually describe and evaluate them in natural language [8], such as 1 T generates a little bit pollution, costs much money, has rare side effects during diagnosis 2 T generates a lot of pollution, costs a little money, has relatively high side effects during diagnosis Based on the above observations, the question of, "Which treatment plan is the sustainable one and how should they be evaluated?"…”
Section: The Proposed Strategymentioning
confidence: 99%
“…Mobile and wearable solutions have a large potential in this domain (Gravenhorst, 2015), especially when their abilities to collect data continuously are considered. The knowledge gained through comprehensive data collection and analysis in large scales benefist not only patients at an individual levels, but also the community (Picard, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Several mobile and wearable applications have been proposed (Gravenhorst, 2015), and are available for download in the Android market and Apple store (iTunes). Despite a significant growth in the availability of mobile apps in the past years, little is known about the characteristics of these applications and the end users' perspectives about them, especially considering novel smart watch applications dedicated to promote mental health.…”
Section: Introductionmentioning
confidence: 99%